2016
DOI: 10.3109/09553002.2016.1152412
|View full text |Cite
|
Sign up to set email alerts
|

Survival and SOS response induction in ultraviolet B irradiatedEscherichia colicells with defective repair mechanisms

Abstract: Purpose In this paper, the contribution of different genes involved in DNA repair for both survival and SOS induction in Escherichia coli mutants exposed to ultraviolet B radiation (UVB, [wavelength range 280-315 nm]) was evaluated. Materials and methods E. coli strains defective in uvrA, oxyR, recO, recN, recJ, exoX, recB, recD or xonA genes were used to determine cell survival. All strains also had the genetic sulA::lacZ fusion, which allowed for the quantification of SOS induction through the SOS Chromotest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
2
10
0
Order By: Relevance
“…The recO gene encodes a gap repair protein and is essential for processing DNA damage prior to SOS induction in E . coli [58]. Consistent with the present results, previous research has demonstrated that green tea polyphenols also induced two DNA repair-related genes, lexA and recN , in P .…”
Section: Resultssupporting
confidence: 93%
“…The recO gene encodes a gap repair protein and is essential for processing DNA damage prior to SOS induction in E . coli [58]. Consistent with the present results, previous research has demonstrated that green tea polyphenols also induced two DNA repair-related genes, lexA and recN , in P .…”
Section: Resultssupporting
confidence: 93%
“…Overall, the antigenotoxic and antioxidant activities of these compounds were not related, suggesting that an antioxidant mechanism was not involved in their antigenotoxicity. We have previously shown that E. coli strain defective for OxyR regulon exposure to UV was as sensitive as wild-type phenotype (59). This supports previous findings that indicate cyclobutane pyrimidine dimers (CPD) and 6-4-pyrimidine pyrimidone photoproducts (6-4PP), instead of oxidative DNA damage, as mainly responsible for the genotoxic effects caused by all types of UV radiation (60).…”
Section: Discussionsupporting
confidence: 87%
“…The PQ37 strain used the expression of β‐galactosidase to assay the functional transcription of the sulA gene, whose product is responsible for cellular division blocked in E. coli . Since photoproducts are an obstacle for E. coli chromosome replication, a postirradiation reduction of sulA gene expression in the presence of genoprotective compounds can be considered indicative of DNA photoproduct repair and cellular division recovery . Therefore, we assume that the antigenotoxic effect detected for Lippia EO against UV occurs by reducing photoproducts formation or stimulating their repair on the DNA molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Since CPD are an obstacle for chromosome replication, compound antigenotoxicity detected with SOS chromotest could be linked to inhibition of CPD formation or photoproducts DNA repair with cell division restoration events . Our study used the E. coli PQ37 strain ( uvr A), which is defective for nucleotide excision repair and its sul A gene was not turned off after UV treatment . Therefore, CPD repair can be excluded as potential antigenotoxic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…This radiation controller continuously measured the irradiance, calculated the irradiation dose and switched the lamps after reaching the target dose. The UVB radiation dose used was 10 J m −2 , which induced SOS functions in E. coli PQ37 cells .…”
Section: Methodsmentioning
confidence: 99%